1975
DOI: 10.1136/thx.30.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Silicosis among grindstone cutters in the north of Nigeria.

Abstract: . (1975). Thorax, 30,[389][390][391][392][393][394][395][396][397][398]. Silicosis among grindstone cutters in the north of Nigeria. Many of the grindstones used in Nigerian homes are quarried from sandstone in a small group of villages near Kano in the extreme north of the country. Of an unselected group of 126 stonecutters from two of these villages 49 were found to have radiographic evidence of silicosis, with progressive massive fibrosis in 17.Those with silicosis had worked longer in the quarries than 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The reductions in the overall means of the lung function indices of the 71 subjects were also found to be significant (Table V). These findings reflect some loss of lung function that corresponds to the development of respiratory illness and are more marked than previous observations made by several investigators on the respiratory health effects of silica dusts [Choudat et al 1990;Kalacic, 1973;Pang et al, 1992;Warrel et al, 1975] and cotton dusts [Glindmeyer, 1991;Valic and Zuskin, 1977;Zuskin and Valic, 1972].…”
Section: Discussionsupporting
confidence: 72%
“…The reductions in the overall means of the lung function indices of the 71 subjects were also found to be significant (Table V). These findings reflect some loss of lung function that corresponds to the development of respiratory illness and are more marked than previous observations made by several investigators on the respiratory health effects of silica dusts [Choudat et al 1990;Kalacic, 1973;Pang et al, 1992;Warrel et al, 1975] and cotton dusts [Glindmeyer, 1991;Valic and Zuskin, 1977;Zuskin and Valic, 1972].…”
Section: Discussionsupporting
confidence: 72%
“…Chronic exposure to dust generated from crushing of granite rocks impairs lung function and causes some respiratory and non-respiratory symptoms in quarry workers [ 1 , 2 ]. A particular concern in some quarries is the inhalation of dust containing silica which can lead to silicosis, an irreversible lung disease resulting in inflammation of the lungs and breathing difficulties which progresses even when exposure stops [ 5 , 6 ]. Reports from countries like the United States and China have shown that millions of people exposed to silica dust eventually develop silicosis resulting in many deaths especially among the older workers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even traditional crafts may be associated with pneumoconiosis-for example, grindstone cutting is associated with silicosis in northern Nigeria. 16 Diagnosis will depend on taking a good respiratory history from the patient and a knowledge of the industrial process concerned. 17 A small supply of standard mini Wright peak flow meters is useful for self monitoring at work and at home if work related asthma is identified as a local problem.…”
Section: Additional Pointsmentioning
confidence: 99%